In Vivo Antihyperuricemia Activity of Kelubut Leaf Ethyl Acetate Extract (Passiflora foetida, L.) From Samarinda City - Mochtar, Chaerul Fadly; Faradillah, Ayu; Bakhtiar, Muh Irham; Devi, Reni Selviana; Husna, Qur’anni Akhwatun; Hafidzah, Elva; Varizza, Fathiah Putri; Aisyiyah, Novia Misnawati (Journal of Fundamental and Applied Pharmaceutical Science, 2024)
The development of the times creates shifts in lifestyle and eating patterns that trigger hyperuricemia. Hyperuricemia is generally treated with synthetic drugs, but on the other hand, it causes side effects. So the use of natural ingredients such as kelubut leaves can be an alternative treatment. The purpose of this study was to determine the ethyl acetate extract of kelubut leaves has activity as an anti-hyperuricemia. The research uses experimental research methods with a design in the form of a pretest and posttest design. Mice were used and divided into 5 groups, namely the positive control group, the negative control and the group given the extract with three different doses including doses of 250 mg/Kg BW, 125 mg/Kg BW, and 62.5 mg/Kg BW. Mice will be conditioned by hyperuricemia and given different treatments in each group. Data on uric acid levels were analyzed by Kruskal-Wallis and Mann-Whitney. The results of the study showed that administration of the extract at a concentration of 250 mg/Kg BW reduced uric acid levels as much as the positive control group at 120 minutes, but was not statistically different (p0.05) from the positive control. This study concludes that the ethyl acetate extract of kelubut leaves has anti-hyperuricemic activity at a dose of 250 mg/Kg BW showing the best-reducing activity in reducing uric acid levels in mice.